1998
DOI: 10.2115/fiber.54.10_555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure stimulation to the waist on the skin temperature of the hand.

Abstract: Abstract:Effect of pressure stimulation to the waist on the skin temperature of the hand was examined by thermography in 2 women subjects. They were pressured around their waists on all sides by using a waistband of 2.5 cm width. Pressure stimuli of 2-minute duration were applied twice at 4-minute intervals and their intensities ranged from 5 to 20 Torr (from 6.8 to 27.2 gf/cm2). Waistband pressures, developed between the waistband and the abdominal skin, were measured by a hydrostatic pressure-balanced method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This suggests the frequency of the regular, sustained spikes discharged by the sympathetic nerve in conjunction with the blood flow at the surface of the skin decreased. 21 The clothing pressure for abdomen affects the function of the autonomic nervous system. A nerve plexus of the autonomic nervous system is distributed over the body surface from under the bust to the waist where muscle is thinner than that at the chest and hips.…”
Section: Distribution Of Ebp Over the Whole Bodymentioning
confidence: 99%
“…This suggests the frequency of the regular, sustained spikes discharged by the sympathetic nerve in conjunction with the blood flow at the surface of the skin decreased. 21 The clothing pressure for abdomen affects the function of the autonomic nervous system. A nerve plexus of the autonomic nervous system is distributed over the body surface from under the bust to the waist where muscle is thinner than that at the chest and hips.…”
Section: Distribution Of Ebp Over the Whole Bodymentioning
confidence: 99%
“…It is possible that the pressure may cause the alternation of the autonomic nervous system [4]. It is therefore important to pay careful attention to the level, duration and frequency of pressure being applied to a particular body part [5]. Among body parts, the legs are most insensitive to pressure and commercial compression ware products that reduce swelling of the legs [6] are widely available [7].…”
Section: Opinionmentioning
confidence: 99%
“…Subjects worn the same shortsleeved 100% cotton t-shirt and one of the following: 100% polyester running pants (A), basic compression pants with 8.9 Tex (80D) yarn (B), 8.9 Tex (80D) yarn pants designed to provide partial compression (C), 12.2 Tex (110D) yarn pants with the same design as C (D). Pants A provided almost no compression, pants B supported the lower abdomen and thighs uniformly, and pants C and D provided varying amounts of partial compression, particularly over the lower abdomen and medial thigh [5]. The basic knitting structure of these compression pants were single-rib stitches.…”
Section: Aerobic Exercise With Three Support Pantsmentioning
confidence: 99%
“…Several studies have shown that clothing pressure is found to affect the human body in such ways as heart rate (HR) variability (Morooka et al, 2001;Sugita et al, 2002;Ishimaru et al, 2010), changes in skin temperature (Mitsuno et al, 1998;Yokoi et al, 2006), changes in blood flow (Kawabata et al, 1989;Nakahashi et al, 1998), displacement and deformation of viscera (Watanabe and Tamura, 1976), decrease of salivary secretion (Okura et al, 2000), changes in α wave (Sugita et al, 2002;Horiba et al, 2000), changes in somatosensory evoked potential (Okada, 1995) and improvements to muscle fatigue (Scanlan et al, 2008;Jakeman et al, 2010). However, there has been little research done concerning differences in psychophysiological response depending on physique under clothing pressure.…”
Section: Introductionmentioning
confidence: 99%